UPAYA GURU MADRASAH DALAM PENCEGAHAN BULLYING DI MTs AL-BAQIYATUSSALIHAT NW SANTONG KEC. KAYANGAN - Farizi, Muhamad; Suparman, Suparman; Rulyandi, Rulyandi (SINERGI : Jurnal Riset Ilmiah, 2025)
Bullying is a serious problem that requires a comprehensive approach to its prevention. Effective prevention efforts involve collaboration between schools, families, and communities. Successful strategies focus on creating a supportive environment, education, and early intervention Schools play an important role in bullying prevention.. This type of research uses qualitative that is descriptive. The method used in collecting data is through three ways, namely interviews, observations and documentation. In processing, analyzing this data uses four stages, namely collecting data, reducing data, presenting data and drawing conclusions. To test the validity of this data using triangulation of sources, methods and theories. The results of this study show that: 1) The form of bullying behavior found in MTs Al-Baqiyatussasee NW Santong Kec. Kayangan really needs more attention, there are several forms of bullying behavior such as verbal bullying and physical bullying. 2) There are two factors that cause bullying that are highlighted in MTs Al-Baqiyatussasee NW Santong Kec. Kayangan, namely family factors and peer factors. 3) Bullying prevention efforts There are several ways that madrasas are used to overcome bullying at MTs Al-Baqiyatussasee NW Santong Kec. Kayangan such as: Preventive efforts (giving advice). Curative efforts (giving special attention to students). Coaching or education efforts related to bullying prevention and sanctions so that it does not happen again